Factors affecting the health related quality of life (HRQoL) of lecturers at UiTM Shah Alam / Norin Rahayu Shamsuddin, Dr Adriana Ismail and Prof Madya Dr Shaare Endot - Shamsuddin, Norin Rahayu; Ismail, Adriana; Endot, Shaare (Research Management Institute (RMI), 2011)
Lecturers in varsities and academic institutions are assets of the varsities and institutions. The progress and achievement of a varsity greatly depend on the work performance of their staff mainly the lecturers. In work performance, productivity is one of the most important outcome measures. The productivity of a lecturer is measured by their teaching and research work, in which adds to the faculty academic profile as well as the university profile. Univeristi Teknologi MARA (UiTM) is one of the comprehensive universities in Malaysia that strives to earn the status of a research university (RU). In order for the university to be an RU, the eight criteria listed out by the Ministry of Higher Education (MOHE) are needed for recognition. With increasing number of students enrollment each year and fulfilling the Ninth Malaysia Plan (9MP) of enrolling 200 000 students by the 2010 (Abdullah, 2008) increase the tense especially to the lecturers. The scenario may lessen the quality of life and decrease the health status of a lecturer. There is no doubt that with good health and good quality of life a lecturer is able to give the best teaching ability and conduct best research work. A lecturer who is having problems with her health might affect her teaching ability. There has been preconceived notion that lecturer suffer poor social and poor emotional functioning due to stress brought by excessive teaching, insufficient resource, time and funding research, administrative workload and insufficient recognition and rewards (Gillespie, Walsh, Winefield, Dua, & Stough, 2001). Lecturers and teachers are claimed to be exposed to high risk of stress and occupational burnout (Chan, Lai, Ko, & Boey, 2000; Tsigilis, Zachopoulou, & Grammatikopoulos, 2006). This in turn might also affect their mental health. Quality of life (QOL) displays the aspect of happiness and satisfaction of individual with their life as a whole. The meaning and the state of of QOL is different for each person as well as in a group of people (Centre for Disease Control and Prevention, 2000). Although health is an important determinant of a person's quality of life, however there are other factors that give the impact on the quality of life such as culture, religion, environment, education and finance (Centre for Disease Control and Prevention, 2000; Lam, 1997). The HRQOL become an important health outcome indicator as the number of people with chronic disease and disabilities have increase (Fryback, 2010; Lam, 1997). It encompass all the aspect in QOL that have an effect towards health of a person either physically or mentally (McHorney, 1999). By measuring the HRQoL, it can help in identifying subgroup of people with poor perceived of health and determine the factors that influence their health to improve their QOL.